2022
DOI: 10.1039/d2tc04029h
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of ternary superconducting YCH12 using a novel solid hydrogen source under high pressure

Abstract: Various hydrogen-rich superconductors have been theoretically predicted under high pressure, such as YH10 with the highest superconducting temperature Tc among the binary compounds. Following the theoretical discoveries, the subsequent experimental...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…The electronic properties of AB-(H 2 ) 3 indicated a gradual closure of the band gap with increasing pressure and exhibited T c of 12 K at 240 GPa, primarily driven by acoustic phonon softening mode. In 2022, Fei et al conducted a theoretical investigation on a ternary superconducting compound Y-C-H to identify a potential superconductor that could be synthesized, utilizing adamantane (C 10 H 16 ) as a new solid hydrogen source [141]. The ab initio calculations revealed that the YCH 12 consists of CH 4 motifs, which exhibits an estimated T c of approximately 112 K at 180 GPa.…”
Section: Doping Molecules Into Hydrogen-rich Binary Systemsmentioning
confidence: 99%
“…The electronic properties of AB-(H 2 ) 3 indicated a gradual closure of the band gap with increasing pressure and exhibited T c of 12 K at 240 GPa, primarily driven by acoustic phonon softening mode. In 2022, Fei et al conducted a theoretical investigation on a ternary superconducting compound Y-C-H to identify a potential superconductor that could be synthesized, utilizing adamantane (C 10 H 16 ) as a new solid hydrogen source [141]. The ab initio calculations revealed that the YCH 12 consists of CH 4 motifs, which exhibits an estimated T c of approximately 112 K at 180 GPa.…”
Section: Doping Molecules Into Hydrogen-rich Binary Systemsmentioning
confidence: 99%